An approximate dynamic programming method for unit-based small hydropower scheduling - Ji, Yueyang; Wei, Hua (Frontiers in Energy Research, 2022)
Hydropower will become an important power source of China’s power grids oriented to carbon neutral. In order to fully exploit the potential of water resources and achieve low-carbon operation, this paper proposes an approximate dynamic programming (ADP) algorithm for the unit-based short-term small hydropower scheduling (STSHS) framework considering the hydro unit commitment, which can accurately capture the physical and operational characteristics of individual units. Both the non-convex and non-linearization characteristics of the original STSHS model are retained without any linearization to accurately describe the hydropower production function and head effect, especially the dependence between the net head and the water volume in the reservoir, thereby avoiding loss of the actual optimal solution due to the large error introduced by the linearization process. An approximate value function of the original problem is formulated via the searching table model and approximate policy value iteration process to address the “curse of dimensionally” in traditional dynamic programming, which provides an approximate optimal strategy for the STSHS by considering both algorithm accuracy and computational efficiency. The model is then tested with a real-world instance of a hydropower plant with three identical units to demonstrate the effectiveness of the proposed method.